Characterization of Sound Absorption of Acoustic Sandwich Panels - Abdul Rahim, Kama Shafik (2018)
Acoustic is a branch of physics that studies the properties of sound waves propagation in pursuit of eliminating noise while enhancing the desired frequency. An acoustic sandwich panel is a product designed to attenuate surrounding sound while maintaining the mechanical properties of the panel. Previous studies has shown effective design of acoustic sandwich panels through perforation at one of the panels. However the attenuation properties achieved only covers middle range frequencies which are higher than speech range. There is possibility of design modification which could satisfy sound absorption ability at lower range frequencies. This attribute can be achieved by applying Helmholtz Resonator principle into the design through combination of honeycomb core sandwiched with perforated panels. Thus this project aims to determine the sound absorption properties of Microperforated Panel-Helmholtz Resonator (MPPHR) design. The experimented result can be further utilised to find out nearest theoretical model that describes the properties of MPPHR design. The experimental setup is made to analyse multiple different variables that act as dynamic attribute to control the sound attenuation properties such as the perforation ratios and the size of perforation or apertures. A custom made honeycomb design which possess bigger cell volume than existing design is used to accommodate the perforation variables. An impedance tube apparatus consisting only two microphones allows the reading of absorption coefficient of the samples. Several analytical models which possibly represents the sound absorption mechanism based on mass-spring model is suggested based on the design parameter. The experimental results shows absorption coefficient, α, highest at 0.98 at frequency of 630Hz which is lower than the frequency attenuated by previous research.